Effectiveness and safety of dabigatran in Latin American patients with atrial fibrillation: Two years follow up results from GLORIA-AF registry. (December 2020) - Dubner, Sergio; Saraiva, José Francisco Kerr; Fragoso, Juan Carlos Nunez; Barón-Esquivias, Gonzalo; Teutsch, Christine; Gurusamy, Venkatesh Kumar; Marler, Sabrina; Huisman, Menno V.; Lip, Gregory Y.H.; Zeballos, Cecilia
Abstract: Background: Real-world data from different regions are needed to support the external validity of controlled trials and assess the impact of new oral anticoagulants (NOAC) in clinical practice. Methods: "GLORIA-AF" is a large, ongoing, multicenter, global, prospective registry program in patients with newly diagnosed non-valvular atrial fibrillation (NVAF) at risk of stroke. Newly diagnosed patients with NVAF (within 4.5 months) and a CHA2 DS2 -VASc score ≥ 1 were consecutively enrolled. The study objective was to estimate the incidence rate of stroke and major bleeding after a two year follow up of patients on dabigatran that participated in the "GLORIA-AF" study (Phase II) in Latin America. Results: Latin America included 378 eligible patients that received dabigatran in eight countries (Argentina, Brazil, Chile, Colombia, Ecuador, Mexico, Perú, and Venezuela): 56.3% were male; mean age was 70.3 ± 10.8 years; 43.4% had paroxysmal AF; 36.0% persistent AF and 20.6% permanent AF. Mean CHA2 DS2 -VASc score was 3.2 ± 1.4; mean HAS-BLED score was 1.2 ± 0.8. Incidence rates for clinical events after 2-years of follow-up per 100 patient-years were as follows: stroke 0.33 (95% CI: 0.04–1.17), major bleeding 0.49 (95% CI: 0.10–1.42) and all-cause death 4.06 (95% CI: 2.63–6.00). Persistence with dabigatran at 6, 12 and 24 months was 91%, 86%, and 80%, respectively. Conclusion: These regional data shows the sustained safety and effectiveness of dabigatran over two years of follow-up, consistent with already available evidence. An increase in accessibility and incorporation of NOAC to anticoagulant treatment strategies could potentially have a positive impact on AF stroke prevention in Latin America.